Perancangan Sistem Insentif Berbasis Design Thinking Pada Pengelolaan Sampah Organik - Wijaya, Muhammad Raffly; Ikhwana, Andri; Kurniawati, Rina (Institut Teknologi Garut, 2025)
The problem of household waste in Indonesia is dominated by organic waste, but the level of sorting at source is still low. This study aims to design an incentive system for organic waste management based on maggots using a Design Thinking approach. Data was obtained through interviews based on the Theory of Planned Behavior (TPB), questionnaires administered to 30 respondents from two household communities in West Java, and technical priority analysis using the House of Quality (HOQ). The results of the study show that the main needs of residents include pick-up services, transparent deposit records, flexibility in the form of incentives, and additional rewards. The highest technical priorities were the provision of pick-up services, separate containers, and direct waste collection services. The resulting system design included a flow of deposits, weighing, recording, incentive provision, and strengthening social participation. In conclusion, this system is considered feasible to implement because it meets the needs of residents and has the potential to support the sustainability of maggot-based waste management within the framework of a circular economy.